Implementación de los sistemas de gestión de la seguridad y salud en el trabajo a través de la gerencia de proyectos utilizando Odoo como herramienta de la inteligencia artificial en los Despachos de Abogados y Asesoría Legal. - Rivas Carruyo, Benylé Josefina (Frónesis)
The article is developed as an essay that shows a general vision of the implementation of occupational health and safety management systems through project management using Odoo as an artificial intelligence tool in Law Firms and Legal Consulting. This, with the purpose of using its postulates, by occupational health and safety professionals. Through this analysis and through a descriptive investigation, we reflect on the protection of the health and safety of workers in the workplace, for which the implementation of occupational health and safety management systems is suggested, which according to the ISO Central Secretariat (2018) have the purpose of preventing injuries and deterioration of health associated with work and continuously improving the performance of occupational health and safety. For implementation, it is recommended to develop the planning, organization, direction and control processes associated with project management, supported by Odoo as an artificial intelligence tool for business resource planning.